From the stability pact to ESM: What next? - Claudia M. Buch (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
Europe is struggling with the resolution of the severe debt crisis and is in the process of overhauling its institutional set up. One element of the reform agenda is the European Stability Mechanism (ESM) which is intended to provide liquidity assistance to countries in case financial stability in the Euro Area is at stake. The ESM shall enter into force in July 2012, following ratification of the member states. It will have five instruments at its disposal: direct loans to countries, purchases of assets on the primary or secondary market, contingent credit lines, and funds for bank recapitalization. In this contribution, it is argued that establishing an explicit crisis resolution mechanism is in principle useful. However, the ESM is defined too broadly, and its scope should be limited to the provision of emergency liquidity assistance only under narrowly defined circumstances. Using the option to recapitalize banks might help addressing a potential debt overhang problem. Yet, the current framework has deficiencies in this regard and lacks the necessary backing by complementary institutional reforms, notably a regime for cross-border bank resolution.
Keywords: E61; E63; F55; 330; Euro Area; ESM